ISOLATION AND SELECTION OF FUNGI FROM MATTER AND ORGANIC FERTILIZER PRODUCT JEMBARA BALI’s ORIGIN THAT HAVE THE CAPABILITY TO DISSOLVE THE PHOSPHATE AS BIO-FERTILIZER AGENT - Varitha, Afny; Sugiharta, Arwan; Salim, Marniati (Sainstek : Jurnal Sains dan Teknologi, 2017)
The research about ?The isolation and selection of fungi from matter and organic fertilizer product Jembara Bali?s origin that have the capability to dissolve the phosphate as Bio-fertilizer agent? have been done on February to June 2010, in The Indonesian Science an Research Institution (LIPI) Bogor. This research aimed to isolate the phosphate solvent fungi from the organic fertilizer product, to identify the kinds of fungi as the Bio-Fertilizer agent, to trial the phosphate dissolve in Laboratorial standard, and then to produce the biofertilizer product. The isolation results of the compos experiment (T1.1 and T1.3) and from the factory compos experiment (T2.1 and T2,2) are identified as Aspergillus sp. The sample of compost experiment (T1.2) is identified as Penicillium sp. Whereas, from the sample of an irrigated land (T3.1) is identified as Mycelliasterillia sp. The result of the test in laboratorial scale is resulted the best capability in dissolve the phosphate is Aspergillussp by T2.2 code. This is viewed by the halo zone diameter shaped is bigger than the others fungi?s kind, it is around 4,2 cm. The enzyme PME-aseacitivities have been tested in each fungi?s species such as : T2.2 (Aspergillus sp), T1.2 (Penicilliumsp), and T3.1 (Mycelliasterillia). The Aspergillus spfungi have the enzyme PME-ase activity is biggest, it is around 1,51 unite/gram. In short, the Aspergillus sp is used as the Bio-fertilizer agent.